Media Pluralism and Democratic Consolidation: A Recipe for Success?. (October 2021) - El Issawi, Fatima
The Tunisian political transition has succeeded in building a working, yet fragile governance beyond ideological and political divides. Political debate across media platforms has become open and dynamic, but the media–politics nexus thrives within a complex system of clientelism forged on shifting alliances between politicians and business tycoons, including recapture by agents of the former regime. The media–politics interplay is taking competitive and antagonistic forms, effectively exacerbating polarized conflicts. This paper reflects on the notions of hybrid media systems, agonistic pluralism, and civic culture, based on data collected in a focus group conducted in Tunis in May 2019 that brought together representatives from media, politics, and civil society complemented by interviews with leading journalists and media stakeholders. This paper argues that the relationship between media and politics is interdependent and marked by confrontation and adaption; the uncertainty of the transition is leading to a complex and volatile power struggle in which neither media nor politics have the upper hand in defining the terms of the game. This ambivalent relationship, taking place within a new system of clientelism, has had a mixed outcome on the process of democratic consolidation.